Molecular Typing of Vibrio parahaemolyticus Strains Isolated from Mollusks in the North Adriatic Sea - Rahman, Mohammad Shamsur; Carraro, Roberta; Cardazzo, Barbara; Carraro, Lisa; Meneguolo, Davide Boscolo; Martino, Maria Elena; Andreani, Nadia Andrea; Bordin, Paola; Mioni, Renzo; Barco, Lisa; Novelli, Enrico; Balzan, Stefania; et al. (Foodborne pathogens and disease, 2017)
Vibrio parahaemolyticus is an emerging foodborne pathogen in the Mediterranean, usually associated with shellfish consumption. The increase in the number of outbreaks in Europe is primarily associated with the global warming of the ocean that has a great impact on the spread and genetic selection of waterborne pathogens. The primary role of Italy in Europe's mollusk production, together with the fact that cases of infections with V. parahaemolyticus are not always notified to the European community, highlighted the necessity of acquiring new information about the epidemiological involvement of shellfish products. The aim of the study was to provide useful insights into the first steps of the Risk Assessment associated with V. parahaemolyticus through the molecular characterization of isolates from commercialized mollusks. A total of 102 strains identified as V. parahaemolyticus were investigated as part of a larger sampling (1-year survey) from several shellfish species collected from the Venice lagoon and the North Adriatic sea. All strains were characterized by multilocus sequence typing and tested for the presence of virulence genes (trh and tdh). The study of sampling/environmental factors and epidemiological analyses was performed to describe the behaviors of the different genetic populations. The population structure analysis highlighted three genetic clusters that could be subject to temperature selection during cold (≤15°C) and warm (>16°C) seasons. Moreover, other factors, such as molluscan species (clams/mussels), probably played a role in the distribution of genetic clusters. Although few strains carried the virulence factors (n = 6 trh ), epidemiological links with clinical isolates and a local dissemination of some sequence types were underlined. This work provides a useful background on the genotype spread as a first step in the Hazard Identification in light of future climate changes.